The New Zealand Māori Council claim to the Waitangi Tribunal and water management in New Zealand - White, Paul (New Zealand Science Review, 2012)
The New Zealand Māori Council filed the ‘National Water and Geothermal Resources claim’ with the Waitangi Tribunal in February 2012, in large part due to the Government’s proposal to part-privatise power-generating State-owned enterprises and to foreshadowed changes to property rights suggested in the Government’s Fresh Start for Fresh Water programme (Waitangi Tribunal 2012). This claim represents an important step in the evolution of Māori involvement with water management in New Zealand. However, much has yet to be resolved. In particular, the Waitangi Tribunal has yet to make recommendations to the Crown on ‘Māori residual proprietary rights’ in regards of the water resource. Revision of property rights associated with water consents under the Resource Management Act (1991) could have significant economic and financial implications for the community and water users, and so will require serious consideration by government. It seems likely that current approaches in the water management roles of Māori authorities, including co-management of water resources between Māori and regional councils, will develop further following the Māori Council claim. An increased role for Māori means extra responsibilities. These responsibilities should result in capability development by Māori in water management and science.